The effect of transcranial direct current stimulation on motor sequence learning and upper limb function after stroke. - Fleming, M; Rothwell, J; Sztriha, L; Teo, J; Newham, D (Elsevier, 2017)
Objective To assess the impact of electrode arrangement on the efficacy of tDCS in stroke survivors and determine whether changes in transcallosal inhibition (TCI) underlie improvements. Methods 24 stroke survivors (3–124 months post-stroke) with upper limb impairment participated. They received blinded tDCS during a motor sequence learning task, requiring the paretic arm to direct a cursor to illuminating targets on a monitor. Four tDCS conditions were studied (crossover); anodal to ipsilesional M1, cathodal to contralesional M1, bihemispheric, sham. The Jebsen Taylor hand function test (JTT) was assessed pre- and post-stimulation and TCI assessed as the ipsilateral silent period (iSP) duration using transcranial magnetic stimulation. Results The time to react to target illumination reduced with learning of the movement sequence, irrespective of tDCS condition (p > 0.1). JTT performance improved after unilateral tDCS (anodal or cathodal) compared with sham (p < 0.05), but not after bihemispheric (p > 0.1). There was no effect of tDCS on change in iSP duration (p > 0.1). Conclusions Unilateral tDCS is effective for improving JTT performance, but not motor sequence learning. Significance This has implications for the design of future clinical trials.